2002
DOI: 10.1097/01.lab.0000043124.75633.ed
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of HLA-A Expression Correlates with a Better Prognosis in Colorectal Cancer Patients

Abstract: SUMMARY:To evaluate the prognostic impact of human leukocyte antigen class I (HLA-I) expression on immune surveillance in colorectal cancer, we studied 88 curatively resected tumors for HLA-A and HLA-B/C expression and correlated these data to clinical and histopathological parameters. HLA-A was normal (all tumor cells had HLA expression) in 32%, reduced (HLA-negative and -positive tumor cells coexisted) in 56%, or absent (no tumor cells expressed HLA) in 12% of evaluable cases. HLA-B/C was normal in 47%, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 44 publications
6
104
2
1
Order By: Relevance
“…In addition, we observed that selective HLA-A down-regulation was significantly more frequent in MSI-H colorectal cancers. Menon et al (33) have previously reported an association of HLA-A negativity with a better prognosis in Notably, significant differences between MSI-H and MSS colorectal cancer were restricted to membraneous HLA-A staining, whereas general HLA-A staining differences did not reach statistical significance. These data may point to the functional Previous studies suggested the involvement of proteasome subunits and transporters of antigen presentation in immune evasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, we observed that selective HLA-A down-regulation was significantly more frequent in MSI-H colorectal cancers. Menon et al (33) have previously reported an association of HLA-A negativity with a better prognosis in Notably, significant differences between MSI-H and MSS colorectal cancer were restricted to membraneous HLA-A staining, whereas general HLA-A staining differences did not reach statistical significance. These data may point to the functional Previous studies suggested the involvement of proteasome subunits and transporters of antigen presentation in immune evasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 87%
“…The expression of HLA was categorized as normal when all tumor cells showed membranous expression, heterogeneous when tumor cells without expression coexisted with HLA-expressing tumor cells or absent when none of the tumor cells expressed HLA and the internal control (stroma, leukocytes, endothelium) was positive. 17 As previously described, an ocular grid, with a total surface area of 38 mm 2 , was used at a  200 magnification to count all leukocytes that were located intraepithelially in 25 different tumor fields of the tissue section. 10 Laminin was used to distinguish between intraepithelially, that is, leukocytes in the direct vicinity of tumor cells, and intrastromally located leukocytes (see Figure 1).…”
Section: Microscopic Evaluation Of Tumor Sectionsmentioning
confidence: 99%
“…Expression of MHC class I alleles is frequently abnormal in colorectal cancer. 5 Previous immunohistochemical studies have indicated that loss of MHC class I expression in colorectal cancer is associated with poorly differentiated tumors and with those exhibiting mucinous differentiation. 5,6 No association has been found between overall MHC class I loss and either survival or metastatic spread.…”
mentioning
confidence: 99%
“…5 Previous immunohistochemical studies have indicated that loss of MHC class I expression in colorectal cancer is associated with poorly differentiated tumors and with those exhibiting mucinous differentiation. 5,6 No association has been found between overall MHC class I loss and either survival or metastatic spread. 7,8 Using high-throughput tissue microarray (TMA) technology, 9 we have analyzed MHC class I expression in a series of more than 450 paraffin-embedded colorectal tumor specimens.…”
mentioning
confidence: 99%